Nectar feeding behavior of some butterflies in the botanical garden of Dhaka university - Begum, Murshida; Habiba, Ummey; Howlader, Moksed Ali (Bangladesh Journal of Zoology, 2015)
Nectar feeding behavior of butterflies belonging to the families Nymphalidae, Danaidae, Pieridae, Lycaenidae and Papilionidae were studied in the Botanical garden of Dhaka University. The highest and the lowest duration of searching time was 39 ± 2 and 36 ± 5 seconds respectively for the Catopsila pomona and Zizina otis. The highest and the lowest duration of feeding was 13.0 ± 1 and 9.9 ± 0.9 seconds respectively for the Danaus chrysippus and Zizina otis. The longest proboscis (12.6 ± mm) was recorded in Danaus chrysipus. The deepest corolla (22 ± 5mm) was found in the flower of Cosmos bipinnatus plants. The proboscis of 4 butterfly species named Eurema hecabe, Jononia almana, Catochrysopes strabo and D. chrysipus was highly correlated with the corolla tube of Cosmos bipinnatus, Tephrosia purpurea and Tagetes erecta repectively. Bangladesh J. Zool. 42(1): 85-90, 2014